2019
DOI: 10.1021/acsbiomaterials.9b00071
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial and Antiadhesive Activities of Silver-PTFE Nanocomposite Coating for Urinary Catheters

Abstract: Catheter-associated urinary tract infection (CAUTI) presents a significant health problem worldwide and is associated with increased morbidity and mortality. Herein, a silver-polytetrafluoroethylene (Ag-PTFE) nanocomposite coating for catheters was developed via a facile wet chemistry method. Benefiting from the synergistic effect of Ag and PTFE, the as-prepared Ag-PTFE-coated catheter exhibited enhanced antibacterial and antiadhesive activities against two CAUTI-associated strains: E. coli WT F1693 and S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 54 publications
2
75
0
1
Order By: Relevance
“…As summary, composite materials are developed with the objective to have a synergistic effect between inorganic and organic components, making the combination of these kind of materials into nanocomposites a promising alternative for the prevention of CAUTIs, as well as UTIs treatment. Here, we also showed the tendency to develop NPs as catheters coating (Dayyoub et al, 2017;Redfern et al, 2018;Zhang et al, 2019), along with some studies about innovative methods to design and develop therapy for systemic administration (Mahadevegowda et al, 2018). Also, Lim et al, suggested the use of Ag-PL-NPs by direct inoculation intro de bladder, a tendency shown in other investigators with organic and inorganic NPs, due the advantage that local administration represent (Lim et al, 2015).…”
Section: Use Of Composite Materialsmentioning
confidence: 55%
See 1 more Smart Citation
“…As summary, composite materials are developed with the objective to have a synergistic effect between inorganic and organic components, making the combination of these kind of materials into nanocomposites a promising alternative for the prevention of CAUTIs, as well as UTIs treatment. Here, we also showed the tendency to develop NPs as catheters coating (Dayyoub et al, 2017;Redfern et al, 2018;Zhang et al, 2019), along with some studies about innovative methods to design and develop therapy for systemic administration (Mahadevegowda et al, 2018). Also, Lim et al, suggested the use of Ag-PL-NPs by direct inoculation intro de bladder, a tendency shown in other investigators with organic and inorganic NPs, due the advantage that local administration represent (Lim et al, 2015).…”
Section: Use Of Composite Materialsmentioning
confidence: 55%
“…The antibacterial and antiadhesive abilities of these coated catheters were evaluated against two of the most common uropathogens (E. coli and S. aureus). The anti-adhesion efficacy of Ag-PTFE composite was analyzed by fluorescence microscopy in uncoated, Ag-coated, and Ag-PTFE-coated catheters, (Zhang et al, 2019).…”
Section: Use Of Composite Materialsmentioning
confidence: 99%
“…For example, as a preventative measure to bacterial growth on textiles, various antimicrobial treatments such as quaternary ammonium compounds, triclosan, and chitosan have been incorporated into fibers [ 9 ]; however, those materials often fail to kill every organism effectively. Biocidal nanoparticles including silver [ 10 , 11 , 12 ], copper [ 12 , 13 ], titanium dioxide [ 14 , 15 , 16 ], and zinc oxide [ 17 , 18 , 19 ] are also used, where silver is particularly effective at interfering with bacterial metabolism. However, the adverse effect of those reactive species on human cells is still obscure, and the environmental and toxicological [ 20 , 21 , 22 ] concerns about using nanoparticles still remain.…”
Section: Introductionmentioning
confidence: 99%
“…In many clinical trials, hydrogel catheters are used as the control or the standard of care catheter presumably because that was the type of catheter the hospital was using at that time [27,28]. Hydrogel catheters have being impregnated with silver molecules, bacteriophages, liposomes containing antibiotics, among others [27,60,61,[68][69][70][71]. Furthermore, hydrogel silver-coated catheters have been commonly used in hospital settings [28] but like many of the coatings discussed in this review, evidence for their efficacy is uncertain.…”
Section: Exopolysaccharide-specific Glycoside Hydrolasementioning
confidence: 99%